Odysseus and the Cult of Apollo at Delos - Marks, Jim (Classica - Revista Brasileira de Estudos Clássicos, 2016)
This paper explores literary representations of the cult of Apollo on Delos. This island is, to be sure, mentioned only occasionally in early Greek poetry, but details specific to the cult do appear. Thus, for example, Odysseus describes a palm tree he saw at an altar of Apollo on Delos (Od. 6.162-3), and a third-century inscription from the island mentions just such a feature. References to a palm, altar, and temple at Delos in later classical authors, including Callimachus, Pliny, Cicero, and Plutarch, demonstrate that the Archaic period traditions represented by the Homeric passages continued to shape how successive generations of visitors understood Delos. The material record makes clear that the Greek epic tradition documents a time when Delos was already a well attended sanctuary, and that later constructions at the site attempted to remain consistent with the details preserved in the epics.